MEKANISME PENGELOLAAN ZAKAT PRODUKTIF PADA BADAN AMIL ZAKAT NASIONAL TANAH DATAR - WIDI NOPIARDO (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
The theme of the article is a business based on the principles of Islamic economics. The research objective is: to see productive zakat management mechanism at the Badan Amil Zakat Nasional Tanah Datar. The benefits of research are: to develop strategies in collecting funds and distributing zakat. This study used descriptive qualitative approach. Under the management of zakat institution established by the state will be much more effective execution of the function and its impact in building the welfare of the people. One of zakat management institutions in Indonesia is BAZNAS Tanah Datar. Zakat productive is BAZNAS program Tanah Datar, in 2013 the distribution of productive zakat amounting to 33.21% of the total collection. In 2014 the distribution of productive zakat amounting to 28.81% of the total collection. Whereas in 2015 the distribution of zakat earning 13.67% of the total collection. This study aims to determine the mechanism of productive zakat management conducted by BAZNAS Tanah Datar from 2013 to 2015. Of several mechanisms conducted in 2013-2015 tend to use the same mechanism. A striking difference in the allocation of funds to skim the distribution of zakat productive and differences in the element distribution patterns where in 2013 there was no training of entrepreneurs (life skills), while in 2014 and 2015 no such training, but in 2015 the allocation of funds for training of entrepreneurs is very little compared to the year 2014.